Poststructuralism and its challenges to applied linguistics - Canh, Lê Văn (VNU Journal of Foreign Studies, 2013)
The paper discusses the core tenets of poststructuralism as related to applied linguistics, particularly to foreign language education. The paper aims to raise the challenges to foreign language education in Vietnam. At the same time, the paper suggests what needs to be rigourously researched inVietnam to seek solutions to those challenges.